The Epistemology of Nusantara Qur’anic Exegesis: A Study of Tarjumān al-Mustafīd by Abdul Rauf al-Singkili - Muanas Sholihin; Eka Prasetiawati; Muhammad Nur Amin (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Local Qur’anic exegesis in the Malay Archipelago plays a vital role in shaping the intellectual tradition of Islam in Southeast Asia. One of the most prominent works in this genre is Tarjumān al-Mustafīd by Shaykh Abdur Rauf al-Singkili, widely recognized as the earliest and most comprehensive Qur’anic commentary written in Jawi-Malay. This study aims to examine the epistemological construction of this tafsir, focusing on its sources of interpretation, employed methods, and the validity of its knowledge claims. The research adopts a qualitative approach through library research using descriptive-analytical methods and a historical-philosophical perspective. The primary data source is the Tarjumān al-Mustafīd manuscript, supported by relevant secondary literature. The analysis employs three theories of truth: coherence, correspondence, and pragmatism. The findings reveal that al-Singkili prioritizes the bi al-ra’y method, drawing from classical tafsir works such as Tafsīr al-Jalālain, al-Bayḍāwī, and al-Khāzin, while integrating elements of bi al-ma’tsūr and qirā’āt analysis. His exegetical style is primarily ijmālī (general/holistic), with occasional taḥlīlī (analytical) components. This study concludes that Tarjumān al-Mustafīd demonstrates a consistent epistemological system, contextually relevant, and pragmatically valuable. Its contribution is significant in affirming the intellectual heritage of Nusantara scholars and in providing a foundation for dialogical engagement with contemporary locally grounded Qur’anic studies.